GeoGebra in 2D and 3D as a learning resource in a multi-integration course: a teaching-learning experience: GeoGebra en 2D y 3D como recurso didáctico en un curso de integración múltiple: una experiencia de enseñanza-aprendizaje - Ramírez Santamaría, Bolívar Alonso (2020)
The purpose of this research paper is to present a teaching and learning experience on the use of GeoGebra, in two and three dimensions, as a didactic resource used to study topics related to multiple integration. This educational software was used in classes and evaluation activities in a group of the course Principles of Analysis II, for the Bachillerato and Licenciatura in Mathematics Teaching of the University of Costa Rica, Sede de Occidente. Different information collection techniques were used such as partial exams, questionnaires and observation guides. The main conclusion is that GeoGebra promotes the motivation and understanding of the learners in the study of topics about to integration in several variables.